PENGENTASAN KEMISKINAN ANTARA HARAPAN DAN KENYATAAN: Suatu Evaluasi Kebijakan Pengentasan Kemiskinan di Kecamatan Loloda Utara Kabupaten Halmahera Utara, Maluku Utara - Simson Tondo; Kismartini Kismartini; Ida Hayu Dwimawanti (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
The government’s commitment to alleviate poverty today is highly important. However, the commitment must be followed by an effective policy. The Policy of Home Construction for Poor Family in the form of home renovation activity is the realization of the government’s commitment of North Halmahera Regency to alleviate poverty. The problems was that the activity did not reduce poverty and some houses were improper to reside. The aim of the research was to evaluate the success of the poicy of home construction for poor people considering the indicators of William Dunn evaluation, effectiveness, sufficiency, alignment, responsiveness, and accuracy. The research used qualitative approach with the technique of purposeive to determine key informant. The evaluation results show that the policy was not successful as indicated by the presence of poverty, improper house to reside, no empowerment to the target families, and the program was not the need of the people. Keywords: Policy Evaluation, Poverty Alleviation, Surgical Home